Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) pada Kurikulum Merdeka Kelas X5 di SMA Negeri 9 Maros - Nugrah Alvina; Amriani Amriani; Irmawati thahir; Nasir Nasir (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The independent curriculum requires students to have a Pancasila spirit. Pancasila is the basic philosophy of the Indonesian nation which has democratic characteristics as a manifestation of Pancasila values which must be applied in educational units. Strengthening the Pancasila profile for students is implemented through a project with a democracy theme. This research aims to describe the implementation of the Project for Strengthening the Pancasila Student Profile (P5) with the theme of the voice of democracy as part of planning the implementation of the Independent Curriculum. The research method used is descriptive qualitative. The research involved all class X5 students at SMA Negeri 9 Maros in the 2022/2023 academic year. The data sources for this research come from interviews, observations and documentation studies. The research results showed that students actively participated in the entire series of activities during the 100 lesson hours. The Pancasila Strengthening Project with the theme of democracy provides opportunities for students to practice democratic culture contextually in the community environment.